Making Tapes in Poland: The Compact Cassette at Home. Issue 1 (February 2017) - BOHLMAN, ANDREA F.
ABSTRACT: This article offers a history of the compact cassette in Poland from 1963 to 2015, focusing on its vibrant presence as the medium of choice for unofficial musical culture. I explore tapes' capacity to reveal a history of everyday musical and technological fluencies: as a sonic archive they offer a window into networked epistemologies of sound under state socialism. Listening to homemade tapes – a process that builds on ethnographic encounters with their makers – I explore the work we can hear across the medium's noisy recordings and stress their position at the crossroads of musicology's methodologies. Tape's reusability, so carefully explained in historical anecdotes and technical manuals in the 1960s, facilitated democratic debate for the social movements of the 1980s. The format's fungibility and plurality made it not only a convenient conduit for discussion, but also a medium that – in form and substance – modelled the importance of dissent, revision, and return in political discourse.